PENDEKATAN REALISTIK TERHADAP PEMAHAMAN SISWA PADA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Mira Shabrina, Nuryaen; Sumiati, Nani (STKIP Subang, 2020)
Lack of student understanding of the concept of learning mathematics, causing students to experience difficulties when working on math problems. The ability to understand is very important for students and is a target to be achieved in the learning process. The purpose of this study is to determine the extent of students' understanding through learning mathematics using a realistic approach by comparing mathematics learning directly. And measure student responses to a realistic approach. The population in this study amounted to 265 students with class IV samples totaling 40 students. The experimental class of 20 students came from the SDN Daya Bakti Cijambe. While the control class of 20 students came from SDN Marga Bakti Cijambe. This type of research is quantitative research using a quasi-experimental model with nonequivalent pretest-posttest design design. The results of the study showed an increase in student understanding as seen from the beginning and end of the ability in both classes. In the experimental class increased student understanding by 44.17% and in the control class by 36.94%. While the results of student questionnaire as much as 64% responded positively. It can be concluded that increasing student understanding through realistic learning approaches is higher than increasing student understanding through direct learning, and most students respond positively to realistic approaches.